The making of proficient young EFL learners in a bilingual speaking class: challenges and strategies - Mislina Mislina (Erudita: Journal of English Language Teaching, 2023)
Teachers’ strategies to teach students’ speaking skills are very essential to overcome students’ obstacles in learning to speak. The present study aims to explore the challenges faced by EFL teachers and their strategies in boosting speaking skills to young learners at the elementary level which enacts a bilingual class program. Three primary EFL school teachers volunteered to participate in this study. Framed in a case study approach, data were garnered through observation and semi-structured interviews. The data from these two collection methods were analyzed qualitatively. The study findings have revealed several challenges faced by teachers in teaching speaking to young EFL learners such as lack of vocabulary, missing pronunciation, problems with students’ self-confidence, and speaking in line. In response to these, several strategies were applied by the teachers in teaching speaking to young learners, including discussion, games, picture description, and role-play. This study concludes with some pedagogical implications on how EFL teachers reflect on the enactment of interactive learning strategies that should adapt to the material, conditions, and students’ abilities so that the strategies can be adapted to foster proficient young EFL learners.